2022
DOI: 10.3390/foods11070926
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Cow’s Milk-Based Infant Formulas in the Prevention and Management of Cow’s Milk Allergy

Abstract: Cow’s milk-based infant formulas are the most common substitute to mother’s milk in infancy when breastfeeding is impossible or insufficient, as cow’s milk is a globally available source of mammalian proteins with high nutritional value. However, cow’s milk allergy (CMA) is the most prevalent type of food allergy among infants, affecting up to 3.8% of small children. Hypoallergenic infant formulas based on hydrolysed cow’s milk proteins are commercially available for the management of CMA. Yet, there is a grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 378 publications
(561 reference statements)
1
35
0
Order By: Relevance
“…This may be related to the fact that parents were worried about the lack of pure nutrient intake when amino acid milk powder was an alternative to breast milk and cow's milk. 48 There is a great need for comprehensive and systematic FA-based health education programmes. [49][50][51] On the one hand, it will help parents manage their children's food allergies (FA) correctly and find alternative nutrients to ensure normal growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the fact that parents were worried about the lack of pure nutrient intake when amino acid milk powder was an alternative to breast milk and cow's milk. 48 There is a great need for comprehensive and systematic FA-based health education programmes. [49][50][51] On the one hand, it will help parents manage their children's food allergies (FA) correctly and find alternative nutrients to ensure normal growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the noteworthy findings of this study, the parental burden of parents whose children took in amino acid milk powder was high. This may be related to the fact that parents were worried about the lack of pure nutrient intake when amino acid milk powder was an alternative to breast milk and cow’s milk 48. There is a great need for comprehensive and systematic FA-based health education programmes 49–51.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this stresses that camel milk would not be a suitable protein source for infant formulas for CMA prevention. We hypothesize that donkey and horse milk proteins due to even lower protein homologies with cow's milk proteins, with protein sequence identities of 46–74% [ 5 ] would likewise not provide suitable sources for CMA prevention, whereas goat and sheep milk proteins, with protein sequence identifies to cow's milk proteins of 85–95% [ 5 ] would probably be better options. It has been suggested that a high degree of homology is needed between proteins in order to obtain a bystander effect and drive tolerance towards counterpart proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, camel whey or casein fortifications considerably increased the high radical scavenging activity of the camel milk-based infant formula as compared to those of the commercial infant formula [75]. Infant formula made from digested camel milk had anti-inflammatory properties that were superior to those of the commercial infant formula and bovine milk, indicating that it would be a feasible option for the creation of a hypoallergenic formula for infants who are allergic to bovine milk [75,76]. Additionally, peptic camel whey hydrolysates were examined as potential sources of peptides with antihypertensive properties capable of inhibiting the angiotensin-converting enzyme and renin [77].…”
Section: Fractionation Of Camel Casein and Creammentioning
confidence: 99%